A novel study of virgin coconut oil as an inhibitor against oral microbiata and its remineralisation potential on enamel tooth surface - Abllah, Zurainie (2018)
As for today, dental caries has been reported adding to the significantly high number of oral health problem worldwide. Therefore, demands of alternatives for the classic regime in arresting issues related to oral health are always on the increase. The virgin coconut oil (VCO) is a case in point and has been the focus for decades as it has proven to possess antimicrobial features on both Gram positive and Gram negative bacteria. Recently, there is a patented activated virgin coconut oil (AVCO) that has been reported to have a broad antimicrobial spectrum. However, information regarding the inhibitory of VCO and AVCO against dental caries-associated pathogens are yet lacking. There were four methods used to study the modes of action, which included time-killing assay, crystal violet assay, leakage of cellular materials and morphological analysis using Scanning Electron Microscopy (SEM). All of the tests were done in triplicate. The evaluation of FICI upon combination gives an antagonism and indifference effects. The study on the modes of actions revealed that AVCO was able to cause leakage of the cellular materials at 260 nm and 280 nm and increase cell permeability. Viewing of cells treated with AVCO by SEM showed some physical and morphological alterations indicating that AVCO able to disrupt the cell growth. These findings were able to backing the crucial role of AVCO as a potential antimicrobial agent, thus aid in arresting the problem of dental caries.